Indonesia in ASEAN : vision and reality - Weatherbee, Donald E... (Institute of Southeast Asian Studies, 2013)
The argument here is that, although Indonesia would appear to be the natural leader in Southeast Asia, it has been singularly unsuccessful in putting its stamp on ASEAN. If anything, ASEAN has been put on Indonesia's bebas dan aktif (independent and active) foreign policy stamp through Indonesia's deference to self-constructed obligations to ASEAN solidarity and consensus.
Keywords: Democracy--Indonesia; Islam and state -- Indonesia